Assessment of Factors Influencing Patronage of Hotels in Ikorodu Local Government Area of Lagos State, Nigeria - Olugbemi, M. T.; Solana, O. I.; Adewunmi, R. D.; Aderinto, A.; Ogungbayi, G. B.; Akerele, E. O. (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020DO - 10.58709/kiujhu.v5i1.800.249-255, 2020)
The customer retention is very important for the hotel to maintain the old customer and attract the new customer. This is very difficult job for the hotels and for each company to retain the old customer and for that reason the hotel offers different package for their customers to retain. The study therefore examined the factors influencing patronage of hotels in Ikorodu Local Government Area of Lagos State, Nigeria. The study was based on primary data obtained in a cross-sectional survey of 203 respondents using multi-stage sampling techniques across communities in the Local Government Areas (LGAs). The study data collected were analysed using both descriptive and quantitative techniques. Descriptive techniques and chi-square were used to analyse the data collected. The findings revealed that majority of the respondents were between 25- 34 years of age with an average of 36.2 years. Socio-demographic characteristics revealed that females were (61.6%).  (75.9%) were married; (48.8%) had secondary education, 33.0% had tertiary level formal education and 9.4% had no formal education. The findings of the study revealed that 53.2% had between 4-6 individuals as household members. Substantial percentage of the participants (60.6%) engaged in trading as the main occupation. About 30.0%) had between 5-9 years of experience in their main occupation. Majority (50.2%) of the respondents were members of social group.  Result of the factors affecting patronage of hotel in the study area were staff hygiene and neat uniform (89.2%), attractive outdoor surroundings (100.0%), well maintenance of hotel interior and exterior (100.0%), sanitation of the hotel (58.6%), colour compatibility in common areas of the hotel (59.1%) and  playing of nice music in the hotel (52.7%). The study recommended that hotel managers should provide quality services that will commensurate with the price the customers pay. Since staff performance is seen as insignificant due to known routine services of staff, there should be a constant staff training of relationship marketing and courtesy. Hotels in the study area should ensure the adequacy of these technological facilities in the hotels and also ensure the effectiveness and efficiency of these facilities. Keywords: Hotel, Patronage, Assessment, Performance. Staff